Adaptive memory systems for remembering the salient and the seemingly mundane. (2016) - Ritchey, Maureen; Murty, Vishnu P.; Dunsmoor, Joseph E.
Abstract: In an adaptive memory system, events should be prioritized in memory based on their own significance, as well as the significance of preceding or following events. Here we argue that tag-and-capture models complement the GANE (glutamate amplifies noradrenergic effects) model by describing a mechanism that supports the transfer of memory benefits from one event to the next.